Análise técnica, econômica e ecológica do uso de biogás em célula a combustível de óxido sólido (SOFC) - Colombaroli, Tulio Stefani [UNESP] (2015)
The search for alternative sources of power generation, less harmful to the environment using renewable fuels has aroused great interest in the scientific community. The use of fuel cells has gained ground then. The Solid Oxide Fuel Cell (SOFC) stands out especially for stationary purposes; it presents a high electrical efficiency by enabling use of the heat released during operation and also by the capacity to use a wide range of fuels. The production of biogas through waste to power generation is established in many countries of the world and there are many ecological gains in this use. This dissertation analyzed the association between a solid oxide fuel cell with a biogas steam reformer. By reforming a synthesis gas (hydrogen-rich) is obtained and sent to the fuel cell; a combustion chamber allows to burn hydrogen unreacted in the cell and an air recuperator recycles part of the air that has not been consumed in the cell. Heat exchangers are also used for recovering the energy contained in the exhaust gases in the process and the simultaneous production of hot water. In order to evaluate the attractiveness of this system performance analyzes were conducted according to the Laws of Thermodynamics, then a economic study was performed based on energy currents of the cogeneration system. In the final step, the quantification of system pollutant emissions is made, seeking the determination of carbon dioxide equivalent, pollution indicator and ecological efficiency. It is concluded that the proposed cogeneration system is an interesting option for energy production, with good energy and exergetic performance. Regarding economic aspects, the payback period was considered high, since it is a residential system; this scenario should change, the trend that the compact SOFC reach a lower value with the spread of its use, by increasing the production volume of these. ... (Complete abstract click electronic access below)